2012
DOI: 10.1002/alr.21125
|View full text |Cite
|
Sign up to set email alerts
|

Quality of surgical field during endoscopic sinus surgery: a systematic literature review of the effect of total intravenous compared to inhalational anesthesia

Abstract: Background Adequate surgical field visualization is imperative for successful outcomes in endoscopic sinus surgery (ESS). The type of anesthetic administered can alter a patient’s hemodynamics and impact endoscopic visualization during surgery. We review the current evidence regarding the effect of total intravenous anesthesia (TIVA) compared to inhalational anesthesia (INA) on visualization of the surgical field during ESS. Methods A systematic review of the literature was performed. Ovid MEDLINE, Scopus, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 28 publications
2
53
0
2
Order By: Relevance
“…15,17,21 Although several studies have concluded that TIVA may improve surgical conditions during the endoscopic sinus surgery, 12,13,2224 others could not show a difference, 252628 and more so, those that did, often had severe limitations in design and/or power to preclude an overall recommendation. 10,14,15 Caution is also warranted because different agents are used in TIVA at different combinations and infusion rates; the same is true for different InhA regimen. Moreover, studies are rarely controlled for the effect of the anesthetic regimen on blood pressure or its determinants cardiac output and systemic vascular resistance.…”
Section: Discussionmentioning
confidence: 99%
“…15,17,21 Although several studies have concluded that TIVA may improve surgical conditions during the endoscopic sinus surgery, 12,13,2224 others could not show a difference, 252628 and more so, those that did, often had severe limitations in design and/or power to preclude an overall recommendation. 10,14,15 Caution is also warranted because different agents are used in TIVA at different combinations and infusion rates; the same is true for different InhA regimen. Moreover, studies are rarely controlled for the effect of the anesthetic regimen on blood pressure or its determinants cardiac output and systemic vascular resistance.…”
Section: Discussionmentioning
confidence: 99%
“…3–12 Results from those studies have been inconsistent, with some authors demonstrating improved surgical field visualization and decreased blood loss, while others failed to find significant differences. Recent systematic reviews came to varying conclusions as well, 2,13,14 suggesting that more high-quality research is needed to further define the role of TIVA for ESS.…”
mentioning
confidence: 99%
“…This makes true metaanalysis difficult [4]. Total bleeding during FESS is also relatively low, therefore large sample sizes are required to detect statistically significant differences [5 & ,6].…”
Section: Interpreting the Literaturementioning
confidence: 99%